Mezclas de herbicidas post emergentes en el cultivo de arroz (Oryza sativa L.) cantón Babahoyo en Ecuador - Lozano Beltrán, Heraclio Steeven (2023)
Rice (Oryza sativa L.) is one of the most extensive crops in Ecuador, since it covers more than a third of the country's provisional product area. These weeds can be found between the limits of tolerance in rice production, since they cause direct and indirect damage due to the competition of light, water and nutrients in our crop. The objective of the research is to evaluate a mixture of post-emergence herbicides in rice cultivation. The investigation will be carried out in the area of Palmar, Babahoyo canton in the province of Los Ríos. The Ferón rice variety and treatments with herbicide mixtures (Fenoxaprop-p-ethyl), (Quinclorac + Cyhalofop-butyl), (Propanil), (2,4-D Amine + Picloram), (Pendimethalin) were used. The experimental design of complete randomized blocks was used, with 7 treatments, 4 repetitions, the comparisons of the means will be made with the Tukey test at 5% of statistical significance. For all statistical calculations, the Infostat and Excel computer tools will be used. Treatment 6 where the herbicides (Fenoxaprop – Ethyl) + (Quinclorac + Cyhalofop-butyl) + (Propanil) + (2,4-D Amine + Picloram) + (Pendimethalin) are mixed at doses of 700cc, 1lt, 1.5lt, 400cc, 2lt presented a greater control and efficiency when eliminating the populations that are regularly present in the rice crop at 40 days after planting with an average control of 95% and at 60 days it obtained an average of 100%. .